Advanced plasma technology in purification of diesel engine exhaust - Ang, Ling Kee (2017)
The purpose of this report is to summaries the progress and achievements throughout the course of 2 Semesters worth for the Final Year Project (FYP). Although the results achieved by the prototype was promising, further improvements could still be made to improve the overall effectiveness. A recommendation for future students that may take up this project would be to incorporate magnets using the principles of Halbach array to focus the plasma generated as well as to attempt to reduce the voltage required to achieve the same results.